SPE Annual Technical Conference and Exhibition 2014
DOI: 10.2118/170729-ms
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Foam Pilot in Salt Creek Field, Natrona County, WY: Phase II: Diagnostic Testing and Initial Results

Abstract: In a previous paper we described the laboratory work, reservoir simulation, and initial design of a CO2 Foam Pilot in the Salt Creek Field, Natrona County, WY. In this paper, we review the diagnostic testing and initial results from the pilot including: injection rate profile, production data analysis, injection and production logging, chemical tracers, streamline analysis, and reservoir simulation. Although the CO2 flood has been very successful at Salt Creek, it is recognized that certain isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Foam injection in fractured reservoirs had been investigated by several authors. Norrise et al, 18 Sanders et al, 19 Li et al, 20 and Yu et al 21 had reported several pilots for foam conducted successfully in conventional reservoir rocks. However, some modern studies prove in-situ generation of foam in a single fracture as reported by Buchgraber et al and Kovscek et al 22 , 23 This leads to improved volumetric sweep efficiency and diversion of flow within a carbonate fracture network at the time of co-injection of the gas and surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Foam injection in fractured reservoirs had been investigated by several authors. Norrise et al, 18 Sanders et al, 19 Li et al, 20 and Yu et al 21 had reported several pilots for foam conducted successfully in conventional reservoir rocks. However, some modern studies prove in-situ generation of foam in a single fracture as reported by Buchgraber et al and Kovscek et al 22 , 23 This leads to improved volumetric sweep efficiency and diversion of flow within a carbonate fracture network at the time of co-injection of the gas and surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…There are several field trial/pilot tests conducted in different fields using foam. Scientists and reservoir engineers have conducted in-depth research with a focus on relevant chemicals and how to generate CO 2 foam by varying injection strategies at reservoir conditions. Table lists the location and properties related to some CO 2 foam pilots for selected sandstone and carbonate reservoirs. This section discusses the summary of these five major field trials.…”
Section: Field Applicationsmentioning
confidence: 99%
“…The pilot was initiated in September 2013. Figure shows the project workflow for piloting CO 2 -foam EOR technology. , The inverted five-spot pattern shown in Figure was chosen based on the examination of historical production and injection data was performed in each pattern in the Salt Creek field. The 22-SE30 as an injector for foam injection was located in the center of the pattern, and it was surrounded by four producers.…”
Section: Field Applicationsmentioning
confidence: 99%
“…In situ foaming the injection gas for enhanced oil recovery (EOR) can improve the volumetric sweep efficiency of the gas phase and reduce the common problems associated with the gas-EOR, such as gas channeling and viscous fingering. Several field pilots have been previously applied to decrease the mobility ratio between the injection gas and the in situ oil. Foam has also been tested for conformance control and expanding the mixing zone near the injection well, acid diversion, and aquifer remediation. , Foam in porous media can be generated by simultaneous or alternating injection of the gas phase with the surfactant solution. The latter is more common for the field applications and generally referred to as surfactant-alternating-gas (SAG) .…”
Section: Introductionmentioning
confidence: 99%